COST-EFFECTIVENESS STUDY OF ANTIHYPERTENSIVE DRUGS IN MUMBAI, INDIA : Pharmaceutical Sciences-Applied Sciences - LIMAYE, DNYANESH; KALE, MADHURA; CHITRE, NEHA; DESHPANDE, DEVASHREE; DESAI, RAJ; LIMAYE, VAIDEHI; FORTWENGEL, GERHARD (International Journal of Life Science and Pharma Research, 2018)
Hypertension is a serious global public health problem. It accounts for 10% of all deaths in India and is the leading non-communicable disease. Recent studies have shown that the prevalence of hypertension is 25% in urban and 10% in rural people in India. It exerts a substantial public health burden on cardiovascular health status and health care systems in India. Antihypertensive treatment effectively reduces hypertensionrelated morbidity and mortality. The cost of medications has always been a barrier to effective treatment. The increasing prevalence of hypertension requires use of cost effective treatment for the effective management of the disease. The present study assesses the cost-effectiveness of antihypertensive drugs in patients with hypertension from Mumbai, India. A cross-sectional study was conducted to assess the costeffectiveness of antihypertensive drugs. Face-to-face interviews were conducted by using a validated questionnaire in a total of 136 (66 males, 70 females) patients with hypertension from F-North Ward, Mumbai, India. Cost-effectiveness was determined on the basis of cost of antihypertensive drug/s, efficacy, adverse drug reactions, safety of administration, frequency of administration, and bioavailability. Atenolol was found to be the most cost-effective (INR 5.5/unit of effectiveness), followed by the amlodipine + losartan combination (INR 5.6), amlodipine (INR 6.3), captopril (INR 6.9), amlodipine + lisinopril (INR 9.6), losartan (INR 14.5) and lisinopril (INR 17.2) in the present study. Thirty-eight (28%) patients received combination therapy. Lisinopril prescribed to16 (11.8%) patients was the least cost-effective drug (INR: 17.2/unit of effectiveness). Prescriptions of cost-effective antihypertensive drugs (73.5%) were more common than less cost-effective antihypertensive drugs (26.5%) in hypertensive patients from Mumbai, India. Most of the patients (72%) were prescribed monotherapy in the treatment of hypertension.